2003
DOI: 10.1161/01.cir.0000045665.57256.86
|View full text |Cite
|
Sign up to set email alerts
|

Serum From Patients With Acute Coronary Syndromes Displays a Proapoptotic Effect on Human Endothelial Cells

Abstract: Background-Endothelial apoptosis of atherosclerotic lesions is a possible determinant for the stable-to-vulnerable plaque transition.Recent data support the notion that plaque activation may be a pan-coronary process, advocating the existence of circulating triggers. Methods and Results-Serum from 40 healthy subjects (group 1) and 73 patients with stable angina (nϭ32; group 2) or acute coronary syndromes (nϭ41; group 3) was incubated with human umbilical vein endothelial cells. The percentage of apoptosis by f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(35 citation statements)
references
References 40 publications
(20 reference statements)
1
33
1
Order By: Relevance
“…We have previously reported that serum from patients with acute coronary syndromes (ACS) exerts a pro-apoptotic effect on the endothelium, thus contributing to plaque instability [23]. The results of the current study are the first ones in patients with stable CAD and suggest that even during the chronic stable phases of the disease the endothelium has abnormalities.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…We have previously reported that serum from patients with acute coronary syndromes (ACS) exerts a pro-apoptotic effect on the endothelium, thus contributing to plaque instability [23]. The results of the current study are the first ones in patients with stable CAD and suggest that even during the chronic stable phases of the disease the endothelium has abnormalities.…”
Section: Discussionmentioning
confidence: 53%
“…The most interesting evidence of a possible beneficial effect of perindopril on the endothelium comes from the results at cellular level in which we used a previously validated methodology [23] that allows the measurement of the harder end point of endothelial function. The data suggest that serum from CAD patients is pro-apoptotic and induces a down-regulation of eNOS protein expression and activity.…”
Section: Discussionmentioning
confidence: 99%
“…12 VEGF, stromal derived factor-1 (SDF-1), granulocyte-colony stimulating factor, and B-type natriuretic peptide (BNP) were measured by ELISA (R&D) and by a solid-phase immunoradiometric assay (Shionoria), respectively.…”
Section: Cytokines and B-type Natriuretic Peptidementioning
confidence: 99%
“…TNF-␣, sTNFR-1, sTNFR-2, IL-6, and IL-1ra were measured as previously described, 3,7 with sensitivity and intra-assay and interassay variabilities of 3 pg/mL, Ͻ5.2%, and Ͻ9.9%; 3 pg/mL, Ͻ2.9%, and Ͻ8.8%; 1 pg/mL, Ͻ2.5%, and Ͻ5.1%; 0.7 pg/mL, Ͻ4.2%, and Ͻ6.4%; and 22 pg/mL, Ͻ3.1%, and Ͻ5%, respectively. IL-10 was quantified by Quantikine Immunoassay by R&D with an intra-and inter-assay variabilities of Ͻ5% and 8%, respectively, and a sensitivity of Ͻ3.9 pg/mL.…”
Section: Biochemical Measuresmentioning
confidence: 99%
“…6 Several cytokines, particularly those belonging to the TNF family members, are known to be elevated during MI, 7 but their role in predicting subsequent prognosis remains to be addressed. Therefore, our primary aim was to undertake a systematic evaluation of TNF-␣ and its type 1 (sTNFR-1) and 2 (sTNFR-2) soluble receptors, together with interleukin (IL)-6, IL-1 receptor antagonist (ra), and IL-10, in a consecutive series of MI patients and to correlate them to short-and long-term incidence of death and HF.…”
mentioning
confidence: 99%